Cognitive and Motivational Challenges in Writing: Studying the Relation With Writing Performance Across Students' Gender and Achievement Level. Issue 2 (10th June 2017) - De Smedt, Fien; Merchie, Emmelien; Barendse, Mariska; Rosseel, Yves; De Naeghel, Jessie; Van Keer, Hilde
Abstract: In the past, several assessment reports on writing repeatedly showed that elementary school students do not develop the essential writing skills to be successful in school. In this respect, prior research has pointed to the fact that cognitive and motivational challenges are at the root of the rather basic level of elementary students' writing performance. Additionally, previous research has revealed gender and achievement‐level differences in elementary students' writing. In view of providing effective writing instruction for all students to overcome writing difficulties, the present study provides more in‐depth insight into (a) how cognitive and motivational challenges mediate and correlate with students' writing performance and (b) whether and how these relations vary for boys and girls and for writers of different achievement levels. In the present study, 1, 577 fifth‐ and sixth‐grade students completed questionnaires regarding their writing self‐efficacy, writing motivation, and writing strategies. In addition, half of the students completed two writing tests, respectively focusing on the informational or narrative text genre. Based on multiple group structural equation modeling (MG‐SEM), we put forward two models: a MG‐SEM model for boys and girls and a MG‐SEM model for low, average, and high achievers. The results underline the importance of studying writing models for different groups of students in order to gain more refined insight into the complex interplay between motivational and cognitive challenges related to students' writing performance.